Modelling and prediction approach for engine performance and exhaust emission based on artificial intelligence of sterculia foetida biodiesel - Sebayang A.H.; Milano J.; Shamsuddin A.H.; Alfansuri M.; Silitonga A.S.; Kusumo F.; Prahmana R.A.; Fayaz H.; Zamri M.F.M.A. (Elsevier Ltd, 2023)
Biodiesel; Diesel fuels; Forecasting; Knowledge acquisition; Machine learning; Neural networks; Smoke; Acid pretreatment; Blended fuels; Emission characteristics; Engine performance; Exhausts emissions; Learning machines; Modelling and predictions; Pretreatment process; Refining process; Sterculia foetida; Diesel engines